PENGARUH MODEL TGT DISERTAI PERMAINAN DAM TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROKARBON - Hardani, Dyah Pandu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aims of this research were to determine the difference in learning outcomes between the students given Teams Games Tournament type cooperative learning model with DAM game and the students given cooperative learning model as well as to know the influence of TGT type cooperative model with DAM game on students learning outcomes of class XI SMK N 2 Pontianak on hydrocarbon material. The research method was a quasy experimental research using control group pretest-posttest design. The sampling technique used was random sampling. The research sample was class XI TP A as experiment class and XI TSM as control class. Essay-shaped written tests and unstructured interviews were used as data gathering tools. Mann-Whitney U was performed toward pre test data and revealed that both samples had no difference in initial ability. Analysis of post test data was carried out using independent t-test yielding value Asymp. Sig. (2-tailed) 0.005. It indicated that there was the difference in student learning outcomes between experiment class student and control class. The effect size value obtained was 1.03 and classiffied as high category. Based on Cohen’s table, the previous value indicated that TGT type cooperative learning model gave effect to student’s learning outcomes as 55%. Keywords: TGT, DAM Game, Learning Outcomes, Hydrocarbon